2016
DOI: 10.1007/s12040-016-0732-8
|View full text |Cite
|
Sign up to set email alerts
|

Satellite evidence for no change in terrestrial latent heat flux in the Three-River Headwaters region of China over the past three decades

Abstract: Terrestrial latent heat flux (LE) in the Three-River Headwaters region (TRHR) of China plays an essential role in quantifying the amount of water evaporation and carbon sink over the high altitude Tibetan Plateau (TP). Global warming is expected to accelerate terrestrial hydrological cycle and to increase evaporation. However, direct field observations are lacking in this region and the long-term variability in LE remains uncertain. In this study, we have revised a semi-empirical Penman LE algorithm based on g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
(43 reference statements)
1
1
0
Order By: Relevance
“…In the arid and semi-arid regions, the increased P promoted the water availability for ET, resulting in the increment of ET. The pattern of increasing ET was matched by an increasing P in the western part of the TRHR, which was also confirmed by Yao et al [29], who reported that P was the primary contributor to increasing ET during 1982-2010. However, in well-watered regions, climate (Ta, RH) and vegetation factors were considered to be related more to the ET dynamic.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In the arid and semi-arid regions, the increased P promoted the water availability for ET, resulting in the increment of ET. The pattern of increasing ET was matched by an increasing P in the western part of the TRHR, which was also confirmed by Yao et al [29], who reported that P was the primary contributor to increasing ET during 1982-2010. However, in well-watered regions, climate (Ta, RH) and vegetation factors were considered to be related more to the ET dynamic.…”
Section: Discussionsupporting
confidence: 83%
“…Recently, several satellite-based models and approaches have been developed to estimate the spatiotemporal ET in the TRHR over the last few decades [28]. For instance, based on a revised semi-empirical algorithm, Yao et al [29] illustrated that there was no statistically significant trend in ET over the TRHR during the period 1982-2010. Xu et al [30] found that ET showed a slight decreasing trend at the rate of 3.3 mm/decade from 2000 through 2014 in the TRHR by using an enhanced surface energy balance system (SEBS) algorithm.…”
Section: Introductionmentioning
confidence: 99%